Event risk covenants, design parameters and agency issues: A comparative study of high yield versus investment grade bonds - Manish Tewari (Verslas: Teorija ir praktika / Business: Theory and Practice, 2018)
We analyse security design parameters of 1,115 high yield (HY) and investment grade (IG) event risk covenants (ERC) protected issues between 1986 and 2012 from the agency conflict perspective. We find positive and significant stock price reaction to the issuance of HY but not the IG issues. Although, majority of these issues carry a call provision, we find significant design differences in the call provision between HY and IG issues. We find that HY issues provide strong call protection to mitigate the risk of a call due to ratings upgrade, compromising firm's financial flexibility; resulting financial distress is mitigated by the ERC. IG issues provide weak call protection to fully exploit growth options however, role of ERC is not apparent. We also find evidence of increase in managerial entrenchment due to the presence of ERC in HY firms however, reduction in agency cost of debt supersedes cost of managerial entrenchment.
Keywords: G320; 650; corporate finance; financing; event risk covenants; callable debt; structured provisions; agency conflict